(untitled) (Journal of the College of Basic Education, 2019)
The significant role played by alternative medicine in recent years led us to carry out a simple spectral study of some natural oils used in medical applications. The study highlighted the form of visible – ultraviolet spectroscopy (uv-vis.) analysis as a non-destructive and fast technique in the determination of absorption spectrum of some natural oils which used for medical purposes. Three types of commercial medicinal natural oils namely; Castor, Camphor and Glycerol oils. Five cm3 from every kind of oil was placed in the quartz cell and exposed to radiation in uv and visible spectrum. The most significant value of the absorbance of Castor oil at the wavelength of 340 nm was about 3.2324%, the highest amount of the absorption spectrum is at a wavelength of 320nm and equal to 1.6574 %. The highest value of the absorption spectrum is at a wavelength of 380nm and equal to 0.0401%. The viscosity and density measurements were carried out for all samples.